Connecting the American People: The Effects of New Modes of Communication during the American Presidential Campaign of 2020 - Louise Anglès d’Auriac (Transatlantica)
This study analyzes the notion of “the American people” on the Twitter accounts of Joe Biden (@JoeBiden) and Donald Trump (@realDonaldTrump) during their campaigns for the 2020 presidential elections. This quantitative and qualitative study highlights how different communication strategies transformed the way candidates defined the American people, which entailed a shift in democratic representation and in civic actions. Following a three-step methodology, it starts by underlining the various modes of “emergence” of the people (Rosanvallon 7), thanks to a lexical and rhetorical analysis of the tweets. To that end, a focus on the grammatical form “we” suggests that the communication of the candidates took advantage of the polysemy of the term for strategic purposes. Second, the creation of in-groups and out-groups produced a strict frame which gave “the people” its shape, suggesting a form of “representation as narrative” (Rosanvallon 192) that characterizes contemporary politics. Thirdly, testing the typology of “collective” and “connective” online action, developed by Lance Bennett and Alexandra Segerberg (1), the data reveals that Biden remained the leader of a classic scheme of “collective action,” while Trump’s communication strategy presented some characteristics of a “hybrid” scheme. Contrary to what has often been said of Trump’s controlling persona, our study suggests that his influence on his supporters’ voice has been weaker than Biden’s.